Indo—Netherlands Subalternity in Post-Independence Javanese Literature Social Portrait - Mukhammad Nur Rokhim (Abjad Journal of Humanities & Education, 2023)
The independence of a nation creates a new perspective on specific communities. Those odds with the general view are wrong and mistaken. This situation often happened to Indo-Dutch groups outside politics who were not involved in the hierarchies of past political practices. Indo-Dutch society in post-independence Indonesia is in the flow of national transitional cultural interests. Novel Godhane Prawan Indo Asmara's work tells of cultural pressures that affect the psychology of an Indo-Dutch girl named Evie Tavernier. This paper examines the figure of Evie Tavernier as part of the social reality of post-independence subalternities. The analysis results concluded that the independence of the Indonesian side gave rise to a cultural and identity revolution. The cultural defeat of the West over its colonial lands gave rise to a counter-identity: the East, which has the right to itself. Rapid socio-cultural changes become a dilemma because of the reversal of power. As a minority, even though indigenous figures accept Evie Tavernier, they do not necessarily unite in the mainstream of the majority culture. He remains alone and independent of other identities, out of the vortex of culture around him. He is in the vortex of the cultural power of local figures during his condition of being marginalized by the community association. In Gayatri Spivak's view, the character of Evie Tavernier is a picture of a subaltern or other in the currents of Dutch-Indonesian culture.